Clearance of primary necrotic cells by non-professional phagocytes - Schwegler, Manuela; Wirsing, Anna Maria; Dollinger, Alena J.; Abendroth, Benjamin; Putz, Florian; Fietkau, Rainer; Distel, Luitpold (Biology of the Cell, 2015)
Homotypic internalisation of tumour cells has frequently been observed in tumour tissue sections. Events of non-professional phagocytosis, however, may also occur in normal tissue if the number of dying cells exceeds the phagocytic capacity of professional phagocytes such as macrophages and dendritic cells. The aim of this study was to investigate the molecular background of non-professional phagocytosis of primary necrotic cells by neighbouring tumour cells and normal skin fibroblasts.We demonstrate that homotypic and heterotypic uptake of necrotic cells is a feature common to various cell types. Investigating critical stimuli of necrotic cell clearance we found that non-professional phagocytes require cytoskeleton rearrangement, recognition of phosphatidylserine and GTPase activity of dynamin II, which is normally engaged in endocytosis. Additionally, we have observed an accumulation of adhesion molecule E-cadherin, phosphorylated actin-linker protein ezrin, lysosomal-associated membrane protein 1 and microtubule-associated protein 1 light chain 3 at the site of engulfment. Loss of membrane integrity and an increase in the intracellular level of heat-shock protein 70 in the necrotic cells have also been observed.Our results shed light on the mechanism of necrotic cell removal by tumour cells and normal skin fibroblasts in vitro. It is reasonable to assume that this process has a physiological relevance in inflammation and autoimmune disease in normal tissue as well as in tumours regarding immune cell infiltration. We conclude that necrotic cell clearance by non-professional phagocytes contributes to the phagocytic activity by macrophages and that this process may prevent release of proinflammatory damage-associated molecular pattern molecules.
EVALuna2:18281

Prognostic Value of Homotypic Cell Internalization by Nonprofessional Phagocytic Cancer Cells - Schwegler, Manuela; Wirsing, Anna Maria; Schenker, Hannah; Ott, Laura; Ries, Johannes; Buettner-Herold, Maike; Fietkau, Rainer; Putz, Florian; Distel, Luitpold (BioMed Research International, 2015)
Background. In this study, we investigated the prognostic role of homotypic tumor cell cannibalism in different cancer types. Methods. The phenomenon of one cell being internalized into another, which we refer to as "cell-in-cell event," was assessed in 416 cases from five head and neck cancer cohorts, as well as one anal and one rectal cancer cohort. The samples were processed into tissue microarrays and immunohistochemically stained for E-cadherin and cleaved caspase-3 to visualize cell membranes and apoptotic cell death. Results. Cell-in-cell events were found in all of the cohorts. The frequency ranged from 0.7 to 17.3 cell-in-cell events per mm(2). Hardly any apoptotic cells were found within the cell-in-cell structures, although apoptotic cell rates were about 1.6 to two times as high as cell-in-cell rates of the same tissue sample. High numbers of cell-in-cell events showed adverse effects on patients' survival in the head and neck and in the rectal cancer cohorts. In multivariate analysis, high frequency was an adverse prognostic factor for overall survival in patients with head and neck cancer (p = 0.008). Conclusion. Cell-in-cell events were found to predict patient outcomes in various types of cancer better than apoptosis and proliferation and might therefore be used to guide treatment strategies.
EVALuna2:18246